Analysis of Road Handling Priorities in Pesawaran Regency Comparison of Fuzzy AHP and PKRMS Methods - Anton, Sari; Sulistyorini, Rahayu; Purba, Aleksander; Utami, Chatarina Niken Dwi Wahyuni Setyo Budi; Karami, Muhammad (Universitas Islam 45, 2025)
Effective road management is crucial to ensure the smoothness and safety of the transportation system in Pesawaran Regency. Although various strategies have been implemented to determine road maintenance priorities, challenges remain in fully integrating technical and non-technical elements comprehensively. This study aims to address these shortcomings by comparing two analytical methods, namely the Fuzzy Analytic Hierarchy Process (FAHP) and the Provincial/District Road Management System (PKRMS), and by developing a combined approach expected to yield more accurate and comprehensive priority determinations in road infrastructure management. The research methodology employs both qualitative and quantitative approaches. FAHP is utilised to address uncertainty and subjectivity in decision-making, while PKRMS provides evaluations based on technical data. Analysis results indicate significant differences in road maintenance priorities generated by the two methods. FAHP ranks the Negeri Sakti - Batas Lampung Selatan (177) road segment as the highest priority with a weight of 0.241 whereas PKRMS prioritises the Negara Saka - Krisnowidodo (081) road segment with a TPI value of 76.040. The integration of these two methods produces a more comprehensive priority ranking, with the Lumbi Rejo - Tresno Maju (089) road segment emerging as the top priority with a TPI value of 132.337. This research introduces an integrative approach that combines FAHP and PKRMS, offering a novel solution for determining road maintenance priorities that simultaneously consider both technical and non-technical aspects.